(untitled) (Research, Society and Development, 2022)
The concept of infertility and its predisposing factors are still in the process of being discovered. Nowadays, it is known that most cases of infertility are linked to men and that their routine and life habits are relevant in this regard. The central one was oxidative stress, which stems from alcohol activities like other environmental consumption activities, directly affecting by interference, for example, in the production of spermatogenic substances and not environmentally suitable. After applying the selection criteria, 48 related to male infertility, triggers, among oxidative stress, as therapeutic mechanisms were analyzed, being articles developed for this, using SciELO and PubMed as tools. The influence of factors such as lifestyle, diet and obesity, in addition to the genetic factor, on the etiology of infertility was evidenced. Among the measures, curative measures on cells of genetic studies as well as in the field of natural medicine, still in development and sometimes ignored, together with antioxidant supplements are particularized. After a study of excellence for the construction of a project of better quality, it is necessary to develop a project of excellence of quality for family members, it is necessary to develop a project of excellence for family members in pairs, which offers an education work that is also in family quality studies, directly to employees due to their infertility condition. The present review aims to describe the main causes of male infertility, with emphasis on oxidative stress, as well as the interventions being developed and working on its treatment.